2022
DOI: 10.1039/d1gc03464b
|View full text |Cite
|
Sign up to set email alerts
|

In silico COSMO-RS predictive screening of ionic liquids for the dissolution of plastic

Abstract: Herein we report the screening of 9405 ionic liquids for plastic dissolution using the continuum solvation model (COMSO-RS) and the results are validated with experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 74 publications
3
44
0
Order By: Relevance
“…The COSMO-RS model is a powerful computational approach for calculating equilibrium thermodynamic properties and screening solvents for polymer dissolution. , It requires structural data as the only input information to predict the solubility and other thermodynamic properties of a solute in any solvent environment. The chemical structures of all the studied molecules such as lignin, Cyrene, dimethyl isosorbide (DMI), and water were created and drawn using Avogadro .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The COSMO-RS model is a powerful computational approach for calculating equilibrium thermodynamic properties and screening solvents for polymer dissolution. , It requires structural data as the only input information to predict the solubility and other thermodynamic properties of a solute in any solvent environment. The chemical structures of all the studied molecules such as lignin, Cyrene, dimethyl isosorbide (DMI), and water were created and drawn using Avogadro .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The ILs with lower excess enthalpy, H E , and lower activity coefficient, ln ( γ ), values of lignin should also be cross-checked for viscosity of a solvent. In our previous publication on plastic dissolution in ILs, we predicted the viscosity of ILs using the COSMO-RS model and showed that the predicted values were highly correlated with the experimental viscosities 59 . Therefore, the viscosity of tetrabutylammonium, tetrabutylphosphonium, cholinium, 1-ethyl-3-methylimidazolium, and 1,1-dipropylpyrrolidinium-based cations in combination with amino acid and carboxylate-based anions were predicted using the COSMO-RS model.…”
Section: Parameters That Influence Lignin Dissolutionmentioning
confidence: 77%
“…We then computationally screened thousands of ILs for cellulose and hemicellulose dissolution 27 , 32 , 58 . In addition, we have validated the COSMO-RS model against experimental data for plastic dissolution in ILs and successfully screened 9405 ILs for plastic dissolution 59 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations